Relationship the Five Pillars of Diabetes Mellitus Management with the Quality Life of Diabetes Mellitus Patients - Fatihah Balqis Azzahra; Fakhrudin Nasrul Sani; Endrat Kartiko Utomo; Antonia Soares (OVUM : Journal of Midwifery and Health Sciences, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels in the body. The incidence of diabetes mellitus continues to rise across all sectors of society, necessitating control efforts to prevent further increases each year. The management of diabetes mellitus is categorized into five pillars: education, physical activity, dietary regulation, self-monitoring of blood glucose levels, and adherence to antidiabetic medication. These five pillars aim to help individuals with diabetes control their blood glucose levels, thereby improving their quality of life. This study aims to analyze the relationship between the five pillars of diabetes mellitus management and the quality of life of people with diabetes. A quantitative research method with a cross-sectional design was used, involving 72 respondents selected through purposive sampling. Data for the independent variables were collected using a five-pillar diabetes management questionnaire, while the dependent variable was measured using the Diabetes Quality of Life (DQOL) questionnaire. Data were analyzed using the Spearman Rank test. The result showed that most respondents had good five-pillars management and a good quality of life, with 42 people (58,3%). The test result showed a p-value = 0,000 and an r-value = 0,761, indicating a strong relationship between the five pillars of management and the quality of life of diabetes mellitus patients.